Proximate composition of cashew nut spread complemented with date palm and ripe banana (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluated the proximate composition of cashew nut spread supplemented with date palm and ripe banana to develop a nutritionally enriched product from locally available raw materials. Cashew nuts, dried dates, and ripe bananas were processed into pastes and combined in different proportions using an extreme vertices mixture design. Seven formulations were prepared in varying ratios of cashew nut, date palm, and banana, mixed thoroughly and pasteurized. The spreads were subjected to proximate analysis using standard methods, and significant variations were observed. Moisture content ranged from 5.15–9.02%, protein 10.22–16.36%, fat 10.38–15.27%, ash 4.12–5.45%, fiber 4.34–6.24%, and carbohydrate 51.74–59.63%. The formulation with 70% cashew, 20% date, and 10% banana recorded the highest protein and fat contents, while the blend with 60% cashew, 20% date, and 20% banana had the highest ash content. Increased cashew nut levels contributed to higher protein and fat, whereas dates and bananas enhanced fiber and carbohydrate levels. The findings demonstrate that cashew nut significantly improves protein and fat composition in spreads, while the addition of dates and bananas enhances dietary fiber and carbohydrates. Therefore, cashew nut–based spreads enriched with date palm and ripe banana can serve as nutritious alternatives to conventional spreads, providing consumers with plant-based protein and energy from locally sourced ingredients.
Keywords: Banana; Cashew; Nut; Protein